Water demand prospects for the irrigation in São Francisco River. - FERRARINI, A. dos S. F. (2019)
Abstract: This study analyzed how the irrigation expansion in São Francisco Hydrographic Region (SFRH) would affect the water availability in four specifics physiographic regions into SFRH (Upper, Middle, sub-Middle, and Lower). The TERM-BR model was used to simulate expansion scenarios in irrigated areas aiming to verify the impact in the water use for 2025 and 2035 according to with National Water Resources Plan (PNRH), and Water Resources Plan for the São Francisco River (SFP). The simulations were carried out for areas deemed potentially suitable for irrigation based on the Ministry of National Integration report (MI). The Climatic Water Balance (CWB) was estimated for São Francisco hydrographic region (SFRH) in order to compare regional water supply and demand. Results suggest that cities located in Upper and Middle São Francisco region would present greater irrigation potential due to the water availability and the proximity to neighborhoods that also irrigate. The comparative result of the CWB and the TERM-BR model shown water availability problems in the states of Alagoas and Pernambuco in particular and cities located in São Francisco Lower.